2017
DOI: 10.1038/srep40777
|View full text |Cite
|
Sign up to set email alerts
|

A transcriptome analysis focusing on inflammation-related genes of grass carp intestines following infection with Aeromonas hydrophila

Abstract: Inflammation is a protective response that is implicated in bacterial enteritis and other fish diseases.The inflammatory mechanisms behind Aeromonas hydrophila infections in fish remain poorly understood. In this study, we performed a de novo grass carp transcriptome assembly using Illumina's Solexa sequencing technique. On this basis we carried out a comparative analysis of intestinal transcriptomes from A. hydrophila-challenged and physiological saline solution (PSS/mock) -challenged fish, and 315 genes were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(27 citation statements)
references
References 60 publications
3
22
2
Order By: Relevance
“…This enhanced expression of TLR-4A in infected zebrafish treated with JPtNPs can be correlated to inflammation. Inflammation onset is important for reducing the spread of infectious agents 25 and also for recruitment and activation of immune cells 2628 . Our results shown that infection of zebrafish with A. hydrophila resulted in significant enhancement, (3 h post infection), in the expression of pro-inflammatory cytokines namely IL-1β (11.3-fold), IFN-γ (34-fold), TNF-α (10.24-fold) and iNOS (12.92-fold) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This enhanced expression of TLR-4A in infected zebrafish treated with JPtNPs can be correlated to inflammation. Inflammation onset is important for reducing the spread of infectious agents 25 and also for recruitment and activation of immune cells 2628 . Our results shown that infection of zebrafish with A. hydrophila resulted in significant enhancement, (3 h post infection), in the expression of pro-inflammatory cytokines namely IL-1β (11.3-fold), IFN-γ (34-fold), TNF-α (10.24-fold) and iNOS (12.92-fold) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 58 934 (88.0%) unigenes showed homologous matches in at least one database ( Table 2). The annotation ratio of assembled unigenes higher than previously reported in other sh, such as Hyporthodus septemfasciatus (41.5%), 28 G. przewalskii (77.8%), 25 Cyprinus carpio (81.1%) 29 and Ctenopharyngodon idella (82.8%), 30 slightly lower than that of S. prenanti (94.4%). 27 The high percentage of annotation ratio might be due to many long sequences obtained from transcriptome data and higher average length of unigenes, as well as the abundant sequence databases.…”
Section: Functional Annotationcontrasting
confidence: 57%
“…Another study on the intestinal transcriptome of grass carp ( C. idella ) infected with A. hydrophila has established 315 up regulated and 235 down regulated immune genes, matrix metalloproteinase‐9 gene associated with inflammatory processes and cytokines associated with intestinal inflammation (Song et al . ). Transcriptome examination of M. rosenbergii hepatopancreas in response to Vibriyo parahaemolyticus infection reported 14569 unigenes with many up‐regulated and down‐regulated genes providing insight into the antibacterial mechanism (Rao et al .…”
Section: Current Status Of Transcriptomics In Aquaculturementioning
confidence: 97%